Board Diversity and Sustainability Reporting Practices of Manufacturing Firms in Nigeria - Offiaeli, Grace Amarachukwu; Salawu , Rafiu Oyesola; Nwobu , Obiamaka (International Review of Management and Marketing, 2025)
The study examines the Board Diversity and Sustainability Reporting Practices of Manufacturing Firms in Nigeria from 2014 to 2023. The objective of this study is to investigate the impact of board diversity on sustainability reporting practices in manufacturing firms. Secondary data from published annual reports and stand-alone reports from 2014 to 2023 of companies listed on the Nigerian Exchange Group was obtained. The population of the study consist of all 71 listed manufacturing firms in the Nigerian Exchange group. Random Sampling technique was employed to select 10 firms as the sample size. Panel Least Squares (PLS) method was used to analyse the data. The study employs the Global Reporting Initiative (GRI) framework to measure sustainability reporting, and it analyzes data from the annual reports of the companies. The results demonstrate that board member nationality has a small but positive influence on sustainability reporting, as does the educational qualification of board members. Additionally, the research finds a small but significant relationship between firm size and sustainability reporting. This study recommends that board members should have access to regular training and development opportunities to improve their comprehension of sustainability-related concerns and reporting requirements.